Intertextual Study in Comparative Literature: Folklore of Oedipus and Folklore of Sangkuriang - Dwi Anggraini; Gianira Shola Shafira; Ferra Rossa Lestari (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research is to identify intertextual study in comparative literature of Oedipus folklore and Sangkuriang folklore. The intertextual study of comparative literature in this study aims to obtain identification results regarding affirmations, negations, restorations, and parodies in literary works through folklore. The research used is descriptive qualitative research with descriptive analysis method. The objects used in this research are Oedipus folklore and Sangkuriang folklore. The results of this study show some data obtained from affirmations, negations, and parodies. There are two affirmations obtained in the intertextual study of the Oedipus folklore and the Sangkuriang folklore. There are two negations found in the intertextual study of the Oedipus folklore and the Sangkuriang folklore. There is only one parody found in the intertextual study of the Oedipus folklore and the Sangkuriang folklore. However, restoration in the intertextual study of the two folklores in this study was not found. Abstrak Penelitian ini bertujuan untuk mengidentifikasi adanya kajian intertekstual dalam sastra bandingan antara cerita rakyat “Oedipus” dan cerita rakyat “Sangkuriang”. Kajian intertekstual dalam sastra bandingan dalam penelitian ini ingin memperoleh hasil identifikasi mengenai afirmasi, negasi, restorasi, dan parody dalam karya sastra melalui cerita rakyat. Penelitian yang digunakan ialah penelitian deksriptif kualitatif dengan metode deksriptif analisis. Objek yang digunakan dalam penelitian ini adalah cerita rakyat “Oedipus” dan cerita rakyat “Sangkuriang”. Hasil dari penelitian ini menunjukkan beberapa data yang diperoleh dari afirmasi, negasi, dan parodi. Afirmasi yang diperoleh dalam kajian intertekstual pada cerita rakyat “Oedipus” dan cerita rakyat “Sangkuriang” ada dua afirmasi. Negasi yang ditemukan dalam kajian intertekstual dalam cerita rakyat “Oedipus” dan cerita rakyat “Sangkuriang” ada dua negasi. Parodi yang ditemukan dalam kajian intertekstual dalam cerita rakyat “Oedipus” dan cerita rakyat “Sangkuriang” hanya ada satu parodi. Namun, restorasi dalam kajian intertekstual terhadap kedua cerita rakyat dalam penelitian ini tidak ditemukan. Kata kunci: kajian intertekstual, cerita rakyat, teks transformasi